Implementasi Model Problem-Based Learning (PBL) dalam Pembelajaran PAI Kelas IX di SMP Plus Al Ittihad Selaawi Garut - Syafaatunnisa, Shopiah; Zakiyah, Qiqi Yuliati (Pendidikan Agama Islam STIT Palapa Nusantara, 2025)
This study aims to examine the implementation of the Problem-Based Learning (PBL) model in Islamic Religious Education (PAI) learning at SMP Plus Al-Ittihad Selaawi Garut. This research is a qualitative study using a descriptive qualitative method. Data collection techniques include observation, interviews, and documentation. The findings indicate that the implementation of the PBL model in PAI learning at SMP Plus Al-Ittihad Selaawi Garut consists of planning, implementation, and evaluation stages. In the planning stage, the PAI teacher developed a lesson plan (RPP) aligned with PBL principles, ensuring the material's suitability with the model's characteristics. The implementation stage follows five steps: orienting students to the problem, organizing students for learning, guiding group investigations, developing and presenting the final product, and analyzing and evaluating the problem-solving process. In the evaluation stage, PBL has been effective in enhancing students' understanding, particularly in applicative subjects such as morality (akhlaq) and social life.